2006
DOI: 10.1111/j.1525-1497.2005.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patients’ experiences with individual primary care physicians

Abstract: With considerable national attention on the importance of patient-centered care, this project demonstrates the feasibility of obtaining highly reliable measures of patients' experiences with individual physicians and practices. The analytic findings underscore the validity and importance of looking beyond health plans to individual physicians and sites as we seek to improve health care quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
196
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 35 publications
(33 reference statements)
5
196
1
1
Order By: Relevance
“…Prior analyses of this survey process have confirmed that survey nonresponse does not pose a threat to the validity of the findings, with no differences across physician practices in individuals' propensity to respond to the survey according to age, race, education, and socioeconomic status. 12 We limited our analyses to practice sites with data available on both patient experiences and HEDIS measures (n=334).…”
Section: Practice Site Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Prior analyses of this survey process have confirmed that survey nonresponse does not pose a threat to the validity of the findings, with no differences across physician practices in individuals' propensity to respond to the survey according to age, race, education, and socioeconomic status. 12 We limited our analyses to practice sites with data available on both patient experiences and HEDIS measures (n=334).…”
Section: Practice Site Datamentioning
confidence: 99%
“…16 Patient experience data were derived from MHQP's administration of the ACES instrument, which produces summary measures covering quality of clinical interactions and organizational features of care (Table 2). 12 The survey sample consisted of adults 18 to 64 years of age with at least 1 year of continuous enrollment in one of five participating health plans, and at least one visit with the primary care physician in the last 12 months. The survey was fielded between July and September 2005 using a three-stage mail protocol, 17 beginning with a mailing containing a cover letter on their health plan stationery and a copy of the survey, followed by a reminder post card (2 weeks later) and a second survey packet to nonrespondents (1 week later).…”
Section: Practice Site Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The study questionnaire used is the Ambulatory Care Experiences Survey (ACES), a validated survey that measures patients' experiences with a specific, named PCP and that physician's practice 18 . Patients were asked two questions related to visit continuity.…”
Section: Patient-reported Measuresmentioning
confidence: 99%